Evaluation of environment and cultivar impact on lentil protein, starch, mineral nutrients, and yield. Issue 2 (13th January 2022) - Chen, Chengci; Etemadi, Fatemeh; Franck, William; Franck, Sooyoung; Abdelhamid, Magdi T.; Ahmadi, Jafar; Mohammed, Yesuf Assen; Lamb, Peggy; Miller, John; Carr, Patrick M.; McPhee, Kevin; Zhou, Yi; et al.
Abstract: Lentil ( Lens culinaris Medik.) is an important source of protein, starch, and mineral nutrients in many parts of the world. However, the impact of environment and cultivar on the enrichment of these nutrients is not well understood. Four lentil cultivars ('Avondale', 'CDC Richlea', 'CDC Maxim', and 'CDC Imvincible') varying in color, seed size, and maturity were evaluated at five Montana locations with diverse climatic and soil conditions over 3 yr. Significant cultivar, location, and year effects were found for yield, protein, starch, and minerals. Grain protein concentration was the highest at Moccasin (262 g kg −1 ) and lowest at Richland (246 g kg −1 ), whereas starch concentration was the highest at Richland (455 g kg −1 ) and lowest at Moccasin (441 g kg −1 ). Among cultivars, Avondale was the top yielding cultivar (1965 kg ha −1 ) and adaptable to most of the environments; CDC Imvincible was the top protein producer (265 g kg −1 ); and CDC Richlea is the leading starch producer (456 g kg −1 ). Grain protein concentration was negatively correlated with starch. Lentil grains varied in nutrient concentrations across locations, with the northcentral Montana region producing 10‐ to 20‐times greater selenium concentration than other locations. CDC Maxim had the highest iron (62.1 mg kg −1 ) and zinc (31.5 mg kg −1 ) concentrations. Seed protein concentration was positively correlated with phosphorus, sulfur, copper, and boron. Seed starch is positively correlated with magnesium and manganese. Results suggest that plant breeding and production site selection could enrich lentil nutrient concentrations to help combat malnutrition in the world. Core Ideas: Lentil grain produced at different locations showed significant differences in nutrient concentrations. Different cultivars showed different capacities of enriching protein and minerals. Protein is negatively correlated with starch and positively correlated with certain mineral elements. Plant breeding and production site selection could enhance lentil nutrient concentrations.